COOPERATIVE LEARNING THROUGH TGT TO ENHANCE STUDENT’S BEHAVIOURAL ENGAGEMENT IN AN INCLUSIVE SCHOOL IN YOGYAKARTA - Titis Pahargyan; Monica Ella Harendita (STKIP Persada Khatulistiwa Sintang, 2022)
This research deals with Teams-Games-Tournament (TGT) as one of the cooperative learning methods implemented in an inclusive school. The aim of the research was to examine the student’s behavioral engagement using the TGT in SMP Taman Dewasa IP Yogyakarta. Through a classroom action research, this study attempts to answer: To what extent does the cooperative learning in this classroom action research enhance the students' engagement in an inclusive school? The research was conducted in three cycles and the participants were 21 students at grade VIII. From the observation, questionnaires, and interviews, there was an increase in the behavioral engagement, from 3.02 to 3.2.